Increasing Motivation and Mathematics Learning Achievement in Sequences and Series Materials using PBL Model with Triastra Method - Nugroho, Moh. Hendy (Department of Mathematics, Universitas Negeri Semarang, 2022)
This research attempted to increase motivation and mathematics learning achievement in the sequences and series material. It was in the form of Classroom Action Research (CAR) and used Triastra method, a method which combines Problem Based Learning (PBL), interactive quiz, and structured tasks through the interactive quiz. Two cycles were done by the researcher starting from pre-cycle. Each cycle consisted of planning, implementation, observation, and reflection. 30 students, including 3 male students and 27 female students of the Class X Multimedia 2 of State Vocational High School 1 Kendal or SMK Negeri 1 Kendal in the academic year of 2019/2020 were involved. Their data were collected using test, observation, and questionnaire. To interpret the data, the researcher used descriptive analysis method. Findings showed that there was an increase in the motivation to the high category, namely from 74% in the cycle 1 to 87% in cycle II. In terms of learning achievement, it increased from 23% in the cycle 1 to 47% in cycle II, while the mean of the achievement increased from 5.95 in cycle 1 to 7.18 in cycle II. Thus, it is concluded that Triastra method can increase students’ motivation and mathematics learning achievement.